APLIKASI ARANG SEKAM DAN KOTORAN GAJAH PADA HASIL TANAMAN ZUCCHINI - Pramono Hadi; Suwardi; Agung Mugi Widodo (GEMA, 2024)
This study aims to explore the use of husk charcoal and elephant manure as organic fertilizer in increasing the growth and production of zucchini (Cucurbita pepo). Application by using elephant manure (G) and husk charcoal dose (S) on zucchini plant yield specifically on the observation of fruit weight, fruit length and fruit diameter. Using factorial method with two treatments with three replications and continued with DMRT test. Data were analyzed using analysis of variance (ANOVA) followed by Duncan's mean comparison test at the 5% significance level. The results showed that the husk charcoal treatment did not show a significant effect on all observations. The treatment of manure dose showed significantly different effects on the variable of fruit weight and fruit length, but not significantly on the variable of fruit diameter. The combination of treatments showed no significant effect on all variables. The practical implication of this research is to provide an environmentally friendly and sustainable alternative in increasing the yield of zucchini plants organically